(untitled) (World Bulletin of Public Health, 2022)
Chronic apical periodontitis (destructive osteitis) is a focus of chronic intoxication and sensitization of the body, representing a potential threat to the development of acute, chronic osteomyelitis of the jaws. Treatment of chronic destructive osteitis is one of the important problems that a dentist faces in his practice (1). Conservative treatment is aimed at eliminating the microbial flora, stimulating bone regenerative processes in the periapical region, and complete obturation to prevent reinfection of the root canal system and periodontal tissues. It is also the least traumatic method for the patient